Badania pilotażowe serii szkieletowej z XV do XIX wieku odnalezionej przy ulicy marsz. Focha w Bydgoszczy (Kronika Bydgoska, 2012)
The article concems pilot studies of the skeleton series from the churchyard in Focha Street in Bydgoszcz, dating back to the 15th- 19th centuries. Though the collection includes relics of about 500 individuals, 113 were thoroughly examined, and reports were madę on their sex, age, height, non-metrical features, possible pathological changes, and 345 skuli and postcranial skeleton measurements taken with the use of the Martin techniąue. The examinations at this stage were of recognitive and informational character aimed at specifying generał proportions of sex and age of the individuals, and showing whether observation of certain trends and regularities was possible. Other recorded information include many pathological changes caused by both disease (bacteria and viruses), hormone and metabolic disorders, nutritional shortages, overloading changes caused by heavy physical work, ordinary involutional changes, and ageing processes. The objective of this work is to indicate an extremely important issue, i.e. the opportunity for familiarisation with the life of Old-Polish Bydgoszcz residents and factors influencing their existence. These factors were or could not always be caught by written sources from the epoch. For Bydgoszcz, such analyses have never been conducted due to the lack of materiał. These studies are thus precursory, which have their unąuestioned scientific value.